The COM-B model: a cross-sectional survey assessing capability, opportunities, and motivation to follow the MIND diet among informal female caregivers of people with Alzheimer's disease and related dementias - Guzman, Jacqueline; Aguiñaga, Susan (Frontiers in Dementia, 2024)
Caring for a person with Alzheimer's disease or dementia has been correlated with poor dietary patterns in caregivers. Dietary patterns like The Mediterranean-DASH diet intervention for neurodegenerative delay (MIND) diet have the potential to reduce the negative health outcomes associated with caregiving. Our objective was to assess the capabilitiesy, opportunities, and motivation of caregivers to follow the MIND diet using the COM-B model approach.Method: Female caregivers (n = 299, mage = 37.7 ± 13.7) participated in an online survey.Majority were White (72%) and cared for someone with Alzheimer's disease (42.6%). The survey included at least one question for each of the 6 COM-B subcomponents: psychological capability, physical capability, social opportunity, physical opportunity, reflective motivation, and automatic motivation.Results: Most caregivers were not consuming the MIND diet as only 8.4% reported normally eating the MIND diet items. Caregivers (36.5%) were slightly confident or not confident at all in cooking and eating the MIND diet. Participants (67.1%) reported that consuming the MIND diet would somewhat to very much be supported by friends and family. Budget, time, and transportation were selected as the main barriers. Budget, cooking skills, access to food and stores, and family support were the main facilitators.Discussion: Strategies to increase capability, opportunities, and motivation for the MIND diet are needed to improve caregivers' health. Future MIND diet interventions should improve budget planning and cooking skills of caregivers (capabilities), make MIND diet food items accessible to them (opportunity) and incorporate social support from family and friends (motivation).